(Re)Examining the Feminist Interview: Rapport, Gender “Matching,” and Emotional Labour - Thwaites, Rachel (Frontiers in Sociology, 2017)
Rapport is usually considered key to any interview situation: building the right kind of rapport can be the difference between success and failure in obtaining the required data. In feminist research rapport is intended to be of a particular kind: created through mutual sharing, minimal power hierarchies, and a feeling of genuine trust between interviewer and interviewee (Oakley, 1981). There is a tension here of which feminist researchers and scholars should remain critical, as the idea of good feminist rapport can clash with the necessity of ‘getting the data’. Building rapport can entail minimising strongly held viewpoints, working hard on one’s emotions to ensure they do not reveal true thoughts, or suggesting an attitude of trust and mutual understanding that may feel disingenuous. If rapport is often a performance by the researcher, then this can clash with the intended open and honest feminist approach. In some cases, then, building rapport may pose a challenge to genuinely following a feminist approach to the research interview. In this paper I wish to explore this tension in more detail in the context of the one-off interview and to what extent it can be resolved.